Peranan Majelis Taklim Mardhotillah Dalam Internalisasi Nilai-Nilai Keislaman - Baryanto Baryanto (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Majelis Taklim is a non-formal educational institution that acts as a place for education, training, and teaching and learning activities to learn, explore, and understand Islamic religious knowledge. The purpose of the establishment of majlis taklim is as a forum to carry out various activities that provide benefits to pilgrims and the community through recitation activities that can foster religious awareness, shape Muslim personality, enhance the ability to read and write Al-Qur'an as well as understanding and guiding towards a view of life that is Islamic. This article aims to find out the role of the Taklim Mardhotillah Assembly located in the BTN Idaman Permai housing complex in Air Bang Sub-district, Curup Tengah District in instilling Islamic values in the community. This research uses descriptive qualitative research, is inductive and aimed at describing and analyzing social activities, events, phenomena, perceptions, ethics, and beliefs in Majlis Ta'lim. Data collection techniques are using observation, interview and documentation methods. This study concludes that the role of Majlis Ta'lim Mardhotillah as a place of study that conveys material about increasing aqidah values, sharia values, religious values and socio-religious values in the people of Central Curup District especially BTN Idaman Permai Air Bang housing residents